Pengaruh Konflik Peran dan Stress Kerja Terhadap Kinerja Perawat pada RSU Bunda Padang - Riri Mayliza; Gusvi Eldini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Human resource management (HR) is a method of managing human resources in an organization so that it is able to achieve the organization's goals optimally through developing human resources themselves. Based on the results of testing the first hypothesis, it was found that the motivation variable had a positive and significant effect on nurses at RSU Bunda Padang. So, in this study the first hypothesis (H1) was accepted. Based on the results of testing the second hypothesis, it was found that the Job Stress variable had a positive and significant effect on nurses at RSU Bunda Padang. So, in this study the second hypothesis (H2) was accepted. Role Conflict partially has a positive and significant effect on employee performance at RSU Bunda Padang. Thus, it can be concluded that if role conflict among employees increases, nurse performance will decrease. Job Stress partially has a negative but not significant effect on the performance of nurses at RSU Bunda Padang. Thus it can be concluded that if work stress increases it will not affect employee performance. Role Conflict, Multiple role work stress simultaneously has a positive and significant effect on Nurse Performance at RSU Bunda Padang. Thus it can be concluded that if Role Conflict, Job Stress and Performance increase together, then the performance of nurses will increase.